( sina*sina-cosa*cosa)/cos2a*sina+cos2a*cosa)=0≤a≤π
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 21:45:40
(sina*sina-cosa*cosa)/cos2a*sina+cos2a*cosa)=0≤a≤π(sina*sina-cosa*cosa)/cos2a*sina+cos2a*cosa)=0≤a≤π
( sina*sina-cosa*cosa)/cos2a*sina+cos2a*cosa)=0≤a≤π
( sina*sina-cosa*cosa)/cos2a*sina+cos2a*cosa)=
0≤a≤π
( sina*sina-cosa*cosa)/cos2a*sina+cos2a*cosa)=0≤a≤π
原式=-(cos2a-sin2a)/[cos2a(sina+cosa)]
=-cos2a/[cos2a(sina+cosa)]
=-1/(sina+cosa)
-(1/(Cos[a] + Sin[a]))
-sina/-cos*-sina*cosa
证明 cosa/(1+sina0-sina/(1+cosa)=2(cosa-sina)/(1+sina+cos)cosa/(1+sina)-sina/(1+cosa)=2(cosa-sina)/(1+sina+cos)
若sin(cosa)cos(sina)
cos/(1+sina)-(1-sina)/cosa 化简!是输错了cosa/(1+sina)-(1-sina)/cosa 化简!
求证道数学题.(cosa-sina)/(1+sina+cosa)=cos/(1+sina)-sina/(1+cosa)
求证[sina(1+sina)+cos(1+cosa)][sina(1-sina)+cos(1-cosa)]=sin2a
比较大小:cosa,cos(sina),sin(cosa)
若|cosa|/cosa+sina/|sina|=0,试判断sin(cosa)·cos(sina)的符号
证明(1-cos^2a)/(sina-cosa)-(sina+cosa)/(tan^2-1)=sina+cosa
证明(1-cos^2a)/(sina+cosa)-(sina+cosa)/(tan^2a-1)=sina+cosa
求证(1-cos²a/sina-cosa)-(sina+cosa/tan²a-1)=sina+cosa
sina>cosa,sina
sina+cosa=7/13则5sina+4cos
证明(cosa+sina)^2=1+2cos*sina 急...
sina-cosa
若sin(cosa)乘以cos(sina)
化解,cos根号(1-sinA/1+sinA)+sinA根号(1-cosA/1+cosA)
cos根号(1-sina)(1+sina)+sina根号(1-cosa)(1+cosa)